An Evaluation on the Eating Practices of Students in Culinary Education (Third Sector Social Economic Review, 2025)
This study aims to analyze the eating practices of students enrolled in culinary arts education within the context of individual, economic, socio-cultural, and educational factors. The research was conducted using a case study approach, one of the qualitative research designs. The participants of the study were first- and second-year students enrolled in culinary arts education in Eskişehir, selected using purposive sampling. During the data collection process, a semi-structured interview form was used to allow students to express their experiences in detail. The data obtained were systematically analyzed using content analysis, one of the qualitative data analysis techniques. As a result of the analysis, six main themes affecting students' eating practices were identified. The findings revealed that a significant proportion of students had irregular and unhealthy eating habits; skipping meals, inadequate nutrition, and consumption of processed foods were quite common. The reasons for this situation were found to include lack of time, economic constraints, exorbitant prices in the food sector, the influence of social environment, and low motivation. Culinary education raises awareness among students about healthy eating, but this awareness often does not translate into action. Furthermore, findings indicate that educational content falls short of meeting industry expectations and that practical learning processes are lacking. In this context, it is recommended that vocational education curricula not only focus on industry/technical competencies but also be integrated in a way that develops students' life skills and self-sufficiency in healthy eating.
Keywords: Culinary Education; Eating Practices; Nutritional Habits; Student Experience; Food Economics